METHIMAZOLE RESISTANCE IN GRAVES' DISEASE - Lim, Krizia Marie; Sibulo, Magnolia; Dampil , Oliver Allan (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE In this case series, we present 4 Filipino patients with Graves' disease who range in age from 22 to 51, 3 of whom were female. At first, beta-blockers and methimazole (MMI) were used for treatment. However, even at the highest doses of MMI, hyperthyroidism was not controlled during serial thyroid function monitoring. These patients were deemed to have methimazole resistance. Treatment was shifted to high-dose propylthiouracil (PTU), to which they became responsive, at least initially. After becoming euthyroid or nearly euthyroid, they underwent radioactive iodine ablation (RAIA). Post-ablation, thyrotoxicosis was controlled, and they were maintained on levothyroxine supplementation thereafter. These cases highlight an important yet uncommon clinical entity of methimazole-resistant Graves' disease. The success of the regimen, shifting MMI to PTU, followed by RAIA once euthyroid, offers clinicians a guide to managing these not-so-common cases.